LEASE OF AGRICULTURAL LAND AS AN INSTRUMENT OF STRUCTURAL CHANGES IN AGRICULTURE IN THE CONTEXT OF THE THEORY OF INSTITUTIONAL ECONOMICS - Aneta Suchoń; Rafał Baum (Acta Scientiarum Polonorum. Oeconomia, 2013)
The paper analyzes legal regulations and statistical data on a lease and assesses their influence on structural changes in agriculture. Next, it presents the issue of lease in the context of the theory of institutional economics (in the framework of old and new institutional economics). The research has proved that a lease is an effective instrument of structural changes in the Polish village helping not only to create and enlarge the new farms but also to modernizing the existing ones. Currently, a lessee of agricultural land is an entity which, in order to run an effective business activity, has to conclude various agreements, file applications, invest. The development of a lease is part of a theory which promotes the image of an entrepreneurial person, entangled in social and institutional relationships, who enters into various agreements.